Impact of steroids on the inflammatory response after ischemic acute kidney injury in rats - Fontana, Johann; Yard, Benito A. (Indian journal of nephrology, 2017)
Inflammation plays a crucial role in acute kidney injury (AKI). The current study was designed to analyze the influence of prednisolone treatment on the inflammatory reaction during the first 96 h after AKI induction in a rat model. AKI was induced by unilateral clipping of the renal vessels. The treatment group received prednisolone 5 mg/kg s.c. daily. Infiltration rates of macrophages, leukocytes, and T-cells (24, 96 h) as well as plasma concentrations of the inflammatory markers intercellular adhesion molecule, interleukin-1 beta (IL-1β), IL-18, IL-6, and tumor necrosis factor-alpha (0, 6, 24, 96 h) were determined by fluorescence-activated cell sorting (FACS) analysis only. Ninety-six hours after AKI induction, the prednisolone group demonstrated significantly lower creatinine concentrations compared to the control group (P < 0.05). Twenty-four hours after induction of AKI, a significantly higher rate of infiltrating leukocytes was detectable with FACS analysis in the control group (P < 0.01) with a corresponding significantly higher rate of macrophages after 96 h (P < 0.01). IL-6 and IL-1β demonstrated a peak after 6 h with a significantly higher release in the control group (IL-6: P < 0.01; IL-1β: P < 0.05). In contrast to the control group, the prednisolone group demonstrated no further incline of IL-18 after 24 h. The results demonstrate the importance of stretching the observation period in an ischemia-reperfusion-induced AKI setting beyond the first 24 h. Despite the demonstrated protective effects of a continuous prednisolone application, it seems that this single anti-inflammatory agent will not be able to completely suppress the inflammatory response after an ischemia-reperfusion-induced AKI.
Gesehen am 13.04.2018